2004
DOI: 10.1007/s10654-004-4340-6
|View full text |Cite
|
Sign up to set email alerts
|

Left handedness and spine deformities in early adolescence

Abstract: The aim of this study was to investigate the relation between laterality and spine deformities in early adolescence, with special reference to sex differences. Interviews, anthropometric measurements and clinical examinations of body posture were carried out on a sample of 2546 schoolchildren, aged from 11 to 14 years, in seven elementary schools in the centre of Belgrade. Possible confounding factors (age, sex, body weight and body height) were controlled for. The overall prevalence of spine deformities (scol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 11 publications
5
17
0
2
Order By: Relevance
“…This is similar to results reported by Milenkovic et al (17) who found scoliosis in 7.8% of 11-14 year old pupils. On the other hand Ostojic et al (19) explored the prevalence of scoliosis in 2517 primary school children (7-14 years old) and reported that 33.4% of examinees had spine deformities, from which 11.8% respondents were suspected structural scoliosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is similar to results reported by Milenkovic et al (17) who found scoliosis in 7.8% of 11-14 year old pupils. On the other hand Ostojic et al (19) explored the prevalence of scoliosis in 2517 primary school children (7-14 years old) and reported that 33.4% of examinees had spine deformities, from which 11.8% respondents were suspected structural scoliosis.…”
Section: Discussionsupporting
confidence: 92%
“…Some found high kyphosis prevalence, such as Bogdanovic (15) who reported kyphosis in 43.14% of 11 year old pupils, or Milenković et al (16) who found it in 51.4% of children 7-10 years old. On the other hand, among somewhat older pupils (11-14 years old) kyphosis prevalence of 4% was reported (17). The higher prevalence of kyphosis in younger respondents may be explained by the specificity of their growth period.…”
Section: Discussionmentioning
confidence: 92%
“…Biomechanical factors involving ribs [59-63] and/or vertebrae [64,65,91-93] and spinal cord [64,65,92,93], acting during growth may localize AIS to the thoracic spine and cause the sagittal spinal shape alterations [83-90]. The non-random laterality of thoracic AIS curves has been explained by several factors including handedness, aorta, lungs, diaphragm, pre-existing lateral curve, axial rotation and embryology [367-371]. We suggest that the laterality and site of t horacic, thoracolumbar and lumbar curves is determined, in part, by the location of the putative abnormalities of the LHS-driven mechanism in the hypothalamus and sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2004 survey, it was shown that in 2546 children from ages 11 to 14 in urban areas in Serbia, the AIS incidence was as high as 7.8%, with the incidence in girls 2.7 times higher than that in boys. [13] …”
Section: Introductionmentioning
confidence: 99%